ANALISIS PROFITABILITAS, UKURAN, PERTUMBUHAN DAN AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI - iwan iwan; Muhammad Fahruroji (Universitas Bina Sarana Informatika, 2018)
Abstract – A good corporate funding decision can be seen from its capital structure. The optimal capital structure is a combination of debt and equity that will maximize company performance. This study aims to examine the effect of Profitability, Company Size, Corporate Growth and Asset Structure either partially or simultaneously to the capital structure of manufacturing companies of food and beverage sub sector listed on Indonesia Stock Exchange period 2012-2015.The data used in this research is secondary data sourced from Indonesia Stock Exchange. The sampling technique used is purposive sampling and the samples studied amounted to 7 companies from the population of 14 companies. Technik data analysis used is multiple linear regression and hypothesis testing using t test and f test.The results of this study indicate that partially (1) Profitability has an effect on and negative to Capital Structure, (2) Company Size has no effect and negative to Capital Structure, (3) Company Growth has no effect and positive to Capital Structure, (4) influential and positive to Capital Structure. And simultaneously Profitability, Size Company, Growth Firms and Asset Structures together affect the Capital Structure.Keywords: Capital Structure, Profitability, Company Size, Corporate Growth, Asset Structure